Impact of anesthetics on 3′-[18F]Fluoro-3′- deoxythymidine ([18F]FLT) uptake in animal models of cancer and inflammation - Fuchs, Kerstin; Kukuk, Damaris; Mahling, Moritz; Quintanilla-Martinez, Leticia; Reischl, Gerald; Reutershan, Jörg; Lang, Florian; Roecken, Martin; Pichler, Bernd J.; Kneilling, Manfred (Molecular Imaging, 2013)
The aim of this study was to evaluate the impact of different anesthetics on 3′-[18F]fluoro-3′-deoxythymidine ([18F]FLT) uptake in carcinomas and arthritic ankles. To determine the amount of [ 18F]FLT uptake in subcutaneous CT26 colon carcinomas or arthritic ankles, spontaneously room air/medical air-breathing mice were anesthetized with isoflurane, a combination of medetomidine/midazolam, or ketamine/xylazine. Mice were kept conscious or anesthetized during [18F]FLT uptake before the 10-minute static positron emission tomographic (PET) investigations. [ 18F]FLT uptake in CT26 colon carcinomas and arthritic ankles was calculated by drawing regions of interest. We detected a significantly reduced (4.4 ± 0.9 %ID/cm3) [18F]FLT uptake in the carcinomas of ketamine/xylazine-anesthetized mice compared to the [ 18F]FLT-uptake in carcinomas of medetomidine/midazolam- (7.0 ± 1.5 %ID/cm3) or isoflurane-anesthetized mice (6.4 ± 1.5 %ID/cm3), whereas no significant differences were observed in arthritic ankles regardless of whether mice were anesthetized or conscious during tracer uptake. The time-activity curves of carcinomas and arthritic ankles yielded diverse [18F]FLT accumulation related to the used anesthetics. [18F]FLT uptake dynamics are different in arthritic ankles and carcinoma, and the magnitude and pharmacokinetics of [ 18F]FLT uptake are sensitive to anesthetics. Thus, for preclinical in vivo [18F]FLT PET studies in experimental tumor or inflammation models, we recommend the use of isoflurane anesthesia as it yields a stable tracer uptake and is easy to handle. © 2013 Decker Publishing.
CRIS-Team Scopus Importer:2022-11-17